Delivering clinical studies of exercise in the COVID-19 pandemic: challenges and adaptations using a feasibility trial of isometric exercise to treat hypertension as an exemplar. Issue 3 (17th March 2023) - Farmer, Chris; Santer, Ellie; West, Alan; Darby, John; Rees-Roberts, Melanie; Doulton, Timothy; MacInnes, Douglas; O'Driscoll, Jamie; Borthwick, Rachel; Pellatt-Higgins, Tracy; Gousia, Katerina; Short, Vanessa; et al.
Abstract : The COVID-19 pandemic has significantly impacted on the delivery of clinical trials in the UK, posing complicated organisational challenges and requiring adaptations, especially to exercise intervention studies based in the community. We aim to identify the challenges of public involvement, recruitment, consent, follow-up, intervention and the healthcare professional delivery aspects of a feasibility study of exercise in hypertensive primary care patients during the COVID-19 pandemic. While these challenges elicited many reactive changes which were specific to, and only relevant in the context of 'lockdown' requirements, some of the protocol developments that came about during this unprecedented period have great potential to inform more permanent practices for carrying out this type of research. To this end, we detail the necessary adaptations to many elements of the feasibility study and critically reflect on our approach to redesigning and amending this ongoing project in order to maintain its viability to date. Some of the more major protocol adaptations, such as moving the study to remote means wherever possible, had further unforeseen and undesirable outcomes (eg, additional appointments) with regards to extra resources required to deliver the study. However, other changes improved the efficiency of the study, such as the remote informed consent and the direct advertising with prescreening survey. The adaptations to the study have clear links to the UK Plan for the future of research delivery. It is intended that this specific documentation and critical evaluation will help those planning or delivering similar studies to do so in a more resource efficient and effective way. In conclusion, it is essential to reflect and respond with protocol changes in the current climate in order to deliver clinical research successfully, as in the case of this particular study.